Factores familiares que influyen en la conducta delincuencial de los internos primarios sentenciados por el delito de robo agravado del pabellón c-3 del establecimiento penitenciario de varones el milagro - trujillo, durante el año 2014 - Gonzales Diaz, Karen Alyssa (2015)
In this research that has done at Establecimiento Penitenciario de Varones El Milagro – Trujillo, that has the target to know and relate the “FAMILY FACTORS THAT INFLUENCE DELINQUENT BEHAVIOR OF INTERNAL SENTENCED FOR THE CRIME OF ROBBERY AGGRAVATED FROM PRISON HOUSE C-3 "DURING THE YEAR 2014, THIS WORK HAS BEEN CONDUCTED WITH A SAMPLE OF 55 INTERNS” Through the research has come to know; by the evidence, facts and events, presented by quantitative and qualitative data, various methods such as observation, interview, survey and bibliography used to find information on family factors that influence behavior were applied delinquency of inmates; Likewise the instruments that allowed collecting significant events. In the first chapter the theoretical framework describe family factors and criminal behaviors, as well as present the problem, hypothesis and objectives of the research; in the second chapter present the methods and techniques used in the development of research as well as population and sample, In the third chapter present the results through statistical data obtained from the information gathered during the course of the investigation by questionnaires answered internal presented, also in the fourth chapter discloses the discussion of results through a qualitative analysis. In addition the findings, recommendations and schedules are prepared. Given these results, it is indicated that family factors; types of family and parenting styles have influenced the criminal conduct of intern. They come from dysfunctional families, disorganized with lack of affection, communication, norms, values has led them to choose behaviors and negative attitudes.